The synergetic effects of high temperature gate bias and total ionization dose on 1.2 kV SiC devices. (September 2018) - Zhang, T.; Allard, B.; Bi, J.
Abstract: The synergetic effects of High Temperature Gate Bias (HTGB) (0 h, 162 h, 332 h) and Total Ionization Dose (TID) radiation (0 kGy, 1 kGy, 3 kGy, 5 kGy, 10 kGy) response of 1200 V commercial SiC power MOSFETs were studied, along with annealing characteristics at room temperature. Electrical parameters were investigated with Current-Voltage (I-V) and Capacitance-Voltage (C-V) measurements. Results show that Gate Threshold Voltage (V th ) is sensitive to combination of HTGB and TID. Gate Leakage Current (I gss ) and V th increase while Input Capacitance (C iss ) decrease after HTGB stress. Drain-Source Leakage Current (I dss ) and I gss rise up due to TID radiation while C iss and V th decrease. HTGB mitigates the shift of parameters due to radiation to some extent, especially I dss . No obvious annealing effect was observed at room temperature for one week on all Device Under Tests (DUTs) in this work. Graphical Abstract: Highlights: Threshold voltage is sensitive to both temperature bias stress and radiation. Samples suffered more degradation with increase in total radiation dose. High temperature gate bias could accelerate radiation effect. Room temperature annealing without bias has no clear influence.